Hardiness Dan Stres Kerja Karyawan Restoran Kampoeng Kopi Banaran Bawen - Indah Kurniasih Isnaini; Sutarto Wijono (Jurnal Ilmiah Psyche, 2023)
This study aims to determine the relationship between hardiness and work stress of Kampoeng Kopi Banaran Bawen restaurant employees. This research uses a quantitative approach. The population in this study were employees of the Kampoeng Kopi Banaran Bawen restaurant, totaling 85 employees and the sample used in this study was 42 employees with the sampling technique used was incidental sampling. The data collection method used the hardiness scale from kobasa (1979), which was previously modified by Jimenez, Munoz, Hernandez, & Blanco (2014) consisting of 15 items and the work stress scale from Parker and Decotiis (1983) consisting of 13 items. The results of this study indicate a correlation, namely r=-0.458; p<0.05. This means that there is a negative and significant relationship between hardiness and work stress on Kampoeng Kopi Banaran Bawen restaurant employees. The higher the employee's hardiness, the lower the work stress that will be experienced by the employees of Kampoeng Kopi Banaran Bawen Restaurant and vice versa, the lower the hardiness, the higher the work stress.